Addition of Infiltration Between the Popliteal Artery and the Capsule of the Posterior Knee and Adductor Canal Block to Periarticular Injection Enhances Postoperative Pain Control in Total Knee Arthroplasty: A Randomized Controlled Trial. (August 2019) - Kim, David H.; Beathe, Jonathan C.; Lin, Yi; YaDeau, Jacques T.; Maalouf, Daniel B.; Goytizolo, Enrique; Garnett, Christopher; Ranawat, Amar S.; Su, Edwin P.; Mayman, David J.; Memtsoudis, Stavros G.
Abstract : BACKGROUND: Periarticular injections (PAIs) are becoming a staple component of multimodal joint pathways. Motor-sparing peripheral nerve blocks, such as the infiltration between the popliteal artery and capsule of the posterior knee (IPACK) and the adductor canal block (ACB), may augment PAI in multimodal analgesic pathways for knee arthroplasty, but supporting literature remains rare. We hypothesized that the addition of ACB and IPACK to PAI would lower pain on ambulation on postoperative day (POD) 1 compared to PAI alone. METHODS: This triple-blinded randomized controlled trial included 86 patients undergoing unilateral total knee arthroplasty. Patients either received (1) a PAI (control group, n = 43) or (2) an IPACK with an ACB and modified PAI (intervention group, n = 43). The primary outcome was pain on ambulation on POD 1. Secondary outcomes included numeric rating scale (NRS) pain scores, patient satisfaction, and opioid consumption. RESULTS: The intervention group reported significantly lower NRS pain scores on ambulation than the control group on POD 1 (difference in means [95% confidence interval], −3.3 [−4.0 to −2.7]; P < .001). In addition, NRS pain scores on ambulation on POD 0 (−3.5 [−4.3 to −2.7]; P < .001) and POD 2 (−1.0 [−1.9 to −0.1]; P = .033) were significantly lower. Patients in the intervention group were more satisfied, had less opioid consumption ( P = .005, postanesthesia care unit, P = .028, POD 0), less intravenous opioids ( P < .001), and reduced need for intravenous patient-controlled analgesia ( P = .037). CONCLUSIONS: The addition of IPACK and ACB to PAI significantly improves analgesia and reduces opioid consumption after total knee arthroplasty compared to PAI alone. This study strongly supports IPACK and ACB use within a multimodal analgesic pathway.